2019
DOI: 10.3389/fphar.2019.00936
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Five Active Components Compatibility of Astragali Radix and Angelicae Sinensis Radix Protect Hematopoietic Function Against Cyclophosphamide-Induced Injury in Mice and t-BHP–Induced Injury in HSCs

Abstract: Although the compatibility of Astragali Radix (AR) and Angelicae Sinensis Radix (ASR) has favorable effect on promoting hematopoiesis in traditional Chinese medicine (TCM), the main active components and pharmacological mechanism are unknown. We investigated the five active components and its mechanisms in vitro and in vivo. Five active components of Astragalus glycosides (AST), Formononetin (FRM), Ferulic acid (FRA), Calycosin (CAL), and Calycosin-7-glucoside (CLG), which could be absorbed in intestinal tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Isoflavones are commonly used as health food supplements for their antioxidant properties ( Messina, 2010 ; Romani et al, 2010 ; Zhang et al, 2019 ). There are four isoflavones in AR: calycosin (C) and formononetin (F) as well as two glycoside form C-glycoside and F-glycoside (Ononin).…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavones are commonly used as health food supplements for their antioxidant properties ( Messina, 2010 ; Romani et al, 2010 ; Zhang et al, 2019 ). There are four isoflavones in AR: calycosin (C) and formononetin (F) as well as two glycoside form C-glycoside and F-glycoside (Ononin).…”
Section: Introductionmentioning
confidence: 99%
“…With reference to our previous study [ 6 , 9 ], the intermediate dose of these active components was selected, (AS IV (20 μ g/ml), AS I (7.5 μ g/ml), FRM (12.5 μ g/ml), CAL (10 μ g/ml), CLG (12.5 μ g/ml), and FRA (18 μ g/ml)), and six dosage groups (50% increment/decrement) were designed, respectively. Then, we detected the cell viability of HUVECs using the uniform design method and obtained the linear regression equation, so as to determine the compatible concentration of six active components.…”
Section: Methodsmentioning
confidence: 99%
“…Astragali radix (AR) and Angelicae sinensis radix (ASR) are classic pairs of drugs that invigorate qi and promote blood circulation, and either of them can protect VECs from oxidative damage due to its antioxidant properties. The compatibility of AR with ASR positively affects the proliferation and tubulogenic capacity of endothelial progenitor cells, increases the survival of VECs, and contributes to the protection of the cardiovascular system by inhibiting the apoptosis of endothelial progenitor cells induced by ox-LDL treatment [ 5 , 6 ]. A previous study found that the compatibility of AR and ASR could alleviate vascular endothelial injury; the main active components detected in the plasma after the oral administration of Danggui Buxue Tang decoction were astragaloside IV (AS IV), calycosin (CAL), calycosin-7-O- β -D glucoside (CLG), astragaloside I (AS I), formononetin (FRM), and ferulic acid (FRA) [ 6 , 7 ], and these components may protect the vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…The calycosin-induced EPO expression was mediated by HIF-1 α from western blotting results [ 56 ]. The in vivo experiments showed that calycosin could enhance the number of RBCs, WBCs, PLTs, and content of Hb in peripheral blood and the area of bone marrow hematopoietic tissue [ 57 ]. The serum contents of thrombopoietin, EPO, granulocyte-macrophage colony stimulating factor, colony of CFU-GM, CFU-MK, CFU-E, and BFU-E were also enriched after calycosin treatment [ 57 ].…”
Section: Pharmacological Activities Of Calycosinmentioning
confidence: 99%
“…The in vivo experiments showed that calycosin could enhance the number of RBCs, WBCs, PLTs, and content of Hb in peripheral blood and the area of bone marrow hematopoietic tissue [ 57 ]. The serum contents of thrombopoietin, EPO, granulocyte-macrophage colony stimulating factor, colony of CFU-GM, CFU-MK, CFU-E, and BFU-E were also enriched after calycosin treatment [ 57 ]. The animal experiments showed that this agent reduced G0/G1 cells and increased G2/M cells in hematopoietic stem cells.…”
Section: Pharmacological Activities Of Calycosinmentioning
confidence: 99%